Puma verbs and the Proto-Kiranti verbal agreement system - Sharma, Narayan P. (Gipan, 2019)
The purpose of this paper is to overview the historical status of conjugations observed in the Puma language based on a comparison of Proto-Kiranti verbal agreement system. The provenance of Proto-Kiranti affixal agreement paradigms is presented by investigating the conjugations of Puma. While some Puma suffixes are identical with the Proto-Kiranti morphemes, a few are cognate with the Proto-Kiranti reflexes.